Would customers be willing to use an alternative (chargeable) delivery concept for the last mile?. (June 2021) - Hagen, Tobias; Scheel-Kopeinig, Sabine
Abstract: B2C e-commerce is still one of the fastest growing marketing channels in almost all product categories yielding to less bundled direct-to-consumer deliveries. Last mile deliveries cause costs and emissions especially in urban areas with a high density of e-customers. Therefore, stakeholders in the context of last mile parcel deliveries are interested in implementing efficient, innovative and ecological last mile concepts. Additionally, such concepts must fulfill the requirements and expectations of online customers as parcel recipients because last mile delivery is the critical link between an online purchase and the delivery to the address stated by the customer. In our customer-driven central last mile micro depot (CMD) project a potential analysis was carried out for the implementation of a CMD with the aim of environmentally-friendly and bundled last mile delivery. Our paper tries to close a research gap by examining acceptance and willingness-to-pay for an alternative last mile delivery concept from the perspective of the customer. Our empirical results based on a survey among German major city residents indicate that city residential areas are potentially more suitable for the realization of a CMD-project than other areas. Furthermore, younger and employed inhabitants are most willing to use the CMD. Based on our statistical model we are able to predict values for the willingness to pay per parcel for a specific population of urban inhabitants. A high proportion of the population in cities (60%) would be interested in participating. However, only 36% are willing to pay in addition to the usual parcel delivery charges. 26% are willing to pay €1.00 or more.